The extent to which Governance Standards are Applied in the Scientific Institute in the Riyadh Region from the Point of View of its Leadership and Teaching Staff - Alatram, Ahmed Abdullah; Alidreisi, Mohammed Tawfiq Yousef (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the extent to which educational governance standards are applied in the Scientific Institute in the Riyadh region from the point of view of its leaders and faculty members. The application of educational governance standards in the institute from the point of view of its leaders and faculty members obtained an overall average of (3.86 out of 5), with a degree (high) and at the level of domains. The domain of law enforcement came first, with an average of (4.14), then the domain of justice with an average of (3.79). Transparency averaged (3.65), all of which are at a (large) degree. The domain of obstacles to the application of educational governance standards at the institute got an overall average (3.43 out of 5) with a degree of (large). As for the obstacles, the material obstacles came first with an average of (3.79) and a rating of (large). Then human obstacles with an average of (3.06), and a rating of (medium). The results also revealed that there are no differences due to the experience variable in the transparency criterion, while there are differences in the application of law and justice in favor of those with greater experience. Based on the results, the researcher recommended that officials in Saudi universities and institutes should pay attention to following up the implementation of the field of transparency by employees, and train workers on how to effectively apply the field of transparency during the governance of universities and institutes, and to take care of overcoming all financial difficulties so that they do not constitute an obstacle to the employment of governance. The researcher suggested conducting a study on the extent to which governance standards are applied in institutes from the students' point of view, and developing a proposed vision on how to implement governance in Saudi universities.
Keywords: evaluation; governance; performance; scientific institutes; the viewpoint of leaders and faculty